Exploring factors of adult disabilities satisfaction towards motives of internet use in Malaysia - Haque, A. K. M. Ahasanul; Abd. Rahman, Rozailin; Hashim, Junaidah; Wok, Saodah (Zes Rokman Resources, 2018)
The level of satisfaction that one experiences while using the internet depends on type of disabilities. The internet offers an opportunity for inclusiveness – to view the global community of its users as one while recognizing its rich diversity. Internet technologies have the potential to give persons with disabilities the means to live on a more equitable basis within the global community in a manner that previously was not possible. However, there is lack empirical evidence regarding the factors of satisfaction that motivate adult disabilities toward the use of internet. Hence, this study aims to examine the level of satisfaction usage of the internet and to provide empirical evidences for policy formulation on digital inclusion among persons with disabilities. Stratified random sampling procedure is used for the quantitative research design. Total 805 adult disabilities data collected according to region: North, West, South, East Coast and East Malaysia. Among them only 593 respondents used Internet and answered all questions and considered for analysis. The findings demonstrated that education and learning, sources of information, business, e-commerce, entertainment and religious aspects are significantly associated to adult disabilities satisfaction of internet usage. The major contribution of the study is that it has developed a model for the purpose of determining the significant factors of adult disabilities satisfaction of internet usage. Finally, this study needs to be conducted by using a bigger combination of independent variables with a more comprehensive model and the analysis need to further be expended and carried out using correlation and regression analysis to testify satisfaction effects on motives of Internet use.